(untitled) (Palíndromo, 2025)
This article proposes a reflection on beauty analyzing some paintings by artist Pedro Weingärtner from the Collaço Paulo Collection. Firstly, we present aspects of the artist’s life and work, considering his works in relation to the artistic movements of his contemporaries, especially Naturalism. Next, we discuss the characteristics of the artistic genre in which the artist most distinguished himself: genre painting, seen in a series of paintings whose theme is the life of peasants in the city of Anticoli Corrado, in Italy. This location attracted many artists at the beginning of the 20th century, in search of a particular type of natural, everyday beauty. We then set out to identify and define the painting of self-absorption, a concept coined by art historian Michael Fried, to describe a kind of attitude of absorption, of withdrawal into oneself. In several of Weingärtner’s paintings it is possible to observe this quality in the figures presented. Very specifically in Ceifa, from 1907, a seated figure from the back, which appears to be contemplating the harvest scene in Anticoli. This spectator within the work mirrors the contemporary spectator in an invitation to an attitude of contemplation of the beauty of the scene in which the experience of time is suspended.